2017
DOI: 10.1111/jwas.12436
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of Protein Hydrolysates to a Low‐fishmeal Diet Improves Growth and Health Status of Juvenile Olive Flounder, Paralichthys olivaceus

Abstract: An 11-wk feeding trial was conducted to evaluate three different protein hydrolysates as feed ingredients in high-plant-protein diets for juvenile olive flounder. Five experimental diets were fed to juvenile olive flounder to examine the effect of three different protein hydrolysates on growth performance, innate immunity, and disease resistance against bacterial infection. A basal fishmeal (FM)-based diet was regarded as a high-FM diet (HFM) and a diet containing soy protein concentrate (SPC) as a substitute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
45
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 68 publications
9
45
1
2
Order By: Relevance
“…In this study, tuna hydrolysate (TH) derived from processing by-products was tested in juvenile barramundi and it was found inclusion levels of 5 to 10% enhanced the FBW and SGR. Similar positive growth responses to dietary inclusion of fish hydrolysates have been found in many fish species including olive flounder, Paralichthys olivaceus 19 , yellow croaker, Pseudosciaena crocea 30 and Atlantic salmon, Salmo salar 29 . The improved growth performance in the present study following moderate levels of hydrolysate inclusion may be a result of the improved availability and subsequent uptake of free amino acids and suitable peptide fractions produced during the enzymatic process which may be beneficial for the growth performance of fish 31 .…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…In this study, tuna hydrolysate (TH) derived from processing by-products was tested in juvenile barramundi and it was found inclusion levels of 5 to 10% enhanced the FBW and SGR. Similar positive growth responses to dietary inclusion of fish hydrolysates have been found in many fish species including olive flounder, Paralichthys olivaceus 19 , yellow croaker, Pseudosciaena crocea 30 and Atlantic salmon, Salmo salar 29 . The improved growth performance in the present study following moderate levels of hydrolysate inclusion may be a result of the improved availability and subsequent uptake of free amino acids and suitable peptide fractions produced during the enzymatic process which may be beneficial for the growth performance of fish 31 .…”
Section: Discussionsupporting
confidence: 71%
“…Likewise, Khosravi et al . 19 found that the addition of protein hydrolysates in low FM diets did not alter most of the hematological indices in juvenile olive flounder, Paralichthys olivaceus while some of the health parameters (lysozyme activity, total immunoglobulin) were improved in hydrolysate supplemented groups. In the current study, the concentration of blood glucose was significantly lower in juvenile barramundi fed with 10 to 20% TH included diets compared to those in the control.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In recent years, studies on the effects of protein hydrolysates on aquatic animals have been reported ( Zheng et al, 2013 ; Khosravi et al, 2017 ; Quinto et al, 2018 ). The main sources of protein hydrolysates include two main categories: those obtained from plants and those obtained from animals.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, fermented plant‐based protein concentrate was ineffective at replacing 30% FM in olive flounder diets (Seong et al., 2018). Therefore, in recent studies, incorporations of fishery side streams or protein hydrolysates were evaluated in LFM diets of olive flounder and successful results were observed (Khosravi et al., 2018; Oncul et al., 2018).…”
Section: Introductionmentioning
confidence: 99%